2021
DOI: 10.24925/turjaf.v9i4.792-796.4207
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Some Marine Macroalgae Species from Iskenderun Bay

Abstract: In the present study, the seaweeds belong to Phaeophyaceae (Halopteris scoparia (Linnaeus) Sauvageau 1904, Cystoseria mediterranea Sauvageau 1912), Rhodophaceae (Liagora viscida (Forsskål) C.Agardh 1822, Laurencia nidifica J.Agardh 1852) and Chlorophyceae (Enteromorpha multiramosa Bliding, nom. inval. 1960) collected from nearby Iskenderun-Turkey of Mediterranean Sea were detected for their antimicrobial activities against seven bacterial (Escherichia coli ATCC 35218, Bacillus cereus NRRL B-371, Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Similarly to most species studied, L. viscida aqueous extracts inhibit B. subtilis growth; however, L. viscida is one of the three species that inhibit S. cerevisiae growth as well. These results may indicate that L. viscida is worth further study within the scope of microbiology, as this seaweed has previously shown antimicrobial activity against bacteria and fungi [104]. To this day, and considering the currently studied species, L. viscida remains one of the seaweed species severely lacking research focused on its biotechnological potential.…”
Section: Species-specific Notesmentioning
confidence: 94%
“…Similarly to most species studied, L. viscida aqueous extracts inhibit B. subtilis growth; however, L. viscida is one of the three species that inhibit S. cerevisiae growth as well. These results may indicate that L. viscida is worth further study within the scope of microbiology, as this seaweed has previously shown antimicrobial activity against bacteria and fungi [104]. To this day, and considering the currently studied species, L. viscida remains one of the seaweed species severely lacking research focused on its biotechnological potential.…”
Section: Species-specific Notesmentioning
confidence: 94%